Structure and Evolution of Confined Carbon Species during Methane Dehydroaromatization over Mo/ZSM-5 - Kosinov, Nikolay; Uslamin, Evgeny A; Coumans, Ferdy J A G; Wijpkema, Alexandra S G; Rohling, Roderigh Y; Hensen, Emiel J M (ACS catalysis, 2018)
Surface carbon (coke, carbonaceous deposits) is an integral aspect of methane dehydroaromatization catalyzed by Mo/zeolites. We investigated the evolution of surface carbon species from the beginning of the induction period until the complete catalyst deactivation by the pulse reaction technique, TGA, C NMR, TEM, and XPS. Isotope labeling was performed to confirm the catalytic role of confined carbon species during MDA. It was found that "hard" and "soft" coke distinction is mainly related to the location of coke species inside the pores and on the external surface, respectively. In addition, MoO species act as an active oxidation catalyst, reducing the combustion temperature of a certain fraction of coke. Furthermore, after dissolving the zeolite framework by HF, we found that coke formed during the MDA reaction inside the zeolite pores is essentially a zeolite-templated carbon material. The possibility of preparing zeolite-templated carbons from the most available hydrocarbon feedstock is important for the development of these interesting materials.